Adaptasi Model UTAUT2 pada Penggunaan Teknologi QRIS di Samarinda - Rezki Aguswidya Utami; Sarah Anistia (Program Magister Ilmu Administrasi Bisnis FISIP Universitas Lambung Mangkurat, 2024)
Abstract: This research aims to analyze the factors influencing the intention and behavior of adopting Quick Response Indonesian Standard (QRIS) technology among consumers of Donutmoo.id in Samarinda. The Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) adaptation model serves as the theoretical framework for this study. Using a quantitative approach, this research focuses on Donutmoo.id customers who utilize QRIS technology for their transactions. Data collection was carried out by distributing online questionnaires. Non-probability sampling with the quota sampling method is used to take the required number of respondents. This study included 153 participants. Partial Least Square (PLS) with SmartPLS 3.0 software was used for data analysis. The result of this research shows that positive influence of performance expectancy, effort expectancy, social influence, hedonic motivation, price value, behavioral intention towards use behavior. One variable does not show significant value, namely social influence